2009
DOI: 10.1080/10496470903139470
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal Activity of Nutmeg and Mace (Myristica FragransHoutt.) Against the Vector SnailLymnaea Acuminata

Abstract: The molluscicidal activity of powdered nutmeg and mace (Myristica fragrans Houtt.) against the vector snail Lymnaea acuminata was evaluated. The toxicity of both the spices was time-and dosedependent. The toxicity of mace powder (96 h LC 50 = 28.61 mgL -1 ) was more pronounced than that of nutmeg powder (96 h LC 50 = 36.95 mgL -1 ). Ethanolic extracts of nutmeg and mace were more toxic than their other organic solvent extracts. The ethanolic extract of mace (24 h LC 50 = 13.33 mgL -1 ) was more effective tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Myristica fragrans (Jaiswal and Singh 2009), Ferula asafetida, Syzygium aromaticum and Carum carvi (Kumar and Singh 2006) were identified as having molluscicidal properties against the former species (LC 50 \100 mg l -1 ). On the other hand, some aromatic plants of the Apiaceae family showed satisfactory larvicidal activities against A. aegypti (Lee 2006) and C. pipiens (LC 50 values from 40 to 100 mg l -1 ) (Evergetis et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myristica fragrans (Jaiswal and Singh 2009), Ferula asafetida, Syzygium aromaticum and Carum carvi (Kumar and Singh 2006) were identified as having molluscicidal properties against the former species (LC 50 \100 mg l -1 ). On the other hand, some aromatic plants of the Apiaceae family showed satisfactory larvicidal activities against A. aegypti (Lee 2006) and C. pipiens (LC 50 values from 40 to 100 mg l -1 ) (Evergetis et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Thymol, trans-anethole, pulegone and eugenol displayed good larvicidal activities against A. aegypti thirdinstar larvae (LC 50 values from 27 to 83 mg l -1 after 24 h) (Waliwitiya et al 2009). The purified compounds myristicin (Jaiswal and Singh 2009), limonene and eugenol (Kumar and Singh 2006) were identified as noteworthy molluscicides against L. acuminata (LC 50 = 1.5, 5.8 and 11 mg l -1 after 24 h, respectively). Generally, oxygenated compounds, namely ketones (L-carvone and pulegone), alcohols (geraniol and terpinen-4-ol) and phenols (eugenol, carvacrol and thymol), have revealed good nematotoxic properties (LC 50 from 115 to 754 mg l -1 after 24 h) (Ntalli et al 2010;Caboni et al 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…However, from an ecotoxicological point of view, this chemical is highly toxic against non-target soft-bodied aquatic organisms and leads to marked decline of them in several areas (da Silva et al 2013, but see Andrews et al 1982 for non-toxic effects on humans). To overcome this challenge, some eco-friendly tools have been developed, including the use of plant-borne compounds as molluscicides to control freshwater snails (Chifundera et al 1993;Brackenbury 1999;Lahlou 2003;Radwan et al 2008;Jaiswal and Singh 2009;Kumar et al 2010;Rapado et al 2011;da Silva et al 2013;Teixeira et al 2012;Singh et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One way to reduce the risk of fascioliasis is to delink the life cycle of the flukes by killing the vector snail [ 3 , 4 ]. Recently, it has been reported that Myristica fragrans (Myristicaceae) seed (nutmeg) and aril (mace) have potent molluscicidal activity against Lymnaea acuminata [ 5 ]. The active moieties responsible for the molluscicidal activity are trimyristin and myristicin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%